A Slanted View on the Future of Islamic Fintech and Conventional Fintech in South and Southeast Asian Countries - Mansur, Mansur; Samsuri, Andriani; Nurhayati, Nurhayati; Khoyyilah, K (El-Barka Journal of Islamic Economics and Business, 2022)
Introduction/Main Objectives: This study reviews the presence of Fintech in South and Southeast Asian countries through several categories. Background Problems: Many people doubt the presence of Fintech in South Asia and Southeast Asia as part of a developing country with all its limitations, especially Sharia Fintech. Novelty: Developing Sharia Fintech in South Asian and Southeast Asian countries, which have not spread evenly before. Research Methods: Qualitatively using GFD (Global Findex Database) data collected in 2021, which was then elaborated with 115 research studies (50 from Scopus, 24 from Research Gate, 21 from Google Scholars and 20 from other sources). Finding/Results: The presence of Fintech is more likely to develop rapidly in the Southeast Asia region, not so in the South Asian region. The lneeds of each region are different. It is different if developed by Sharia Fintech (I-Fintech/Islamic Financial Technology). Its potential is almost acceptable in all regions, including in countries that are sensitive to religious issues. Conclusion: It is not only Fintech that is the future of cutting-edge banking, but also the presence of I-Fintech (Islamic Financial Technology) which empirically opens up great opportunities and repositions mainstream financial institutions into traditional banking, including Islamic banking. However, the presence of Fintech and I-Fintech still requires the support of local government policies and the wider community, Muslims and non-Muslims in any part of the world.